Concise Total Synthesis of Helicascolides A, B, and C - Yadav, Jhillu Singh; Reddy, Anugu Bal; Shankar, Kattela Shiva (Synthesis, 2013)
The concise total synthesis of helicascolides A, B, and C has been achieved in seven steps starting from commercially available tiglic aldehyde [(E)-2,3-dimethylacrylaldehyde]. Oppolzer’s sultam aldol, Mukaiyama aldol, and Dess–Martin periodinane oxidation reactions are the key steps involved in the target synthesis.
Keywords: helicascolides A, B, and C; lactones; antifungal agents; asymmetric aldol reactions; total synthesis